VALUE INVESTING DALAM PERSPEKTIF INVESTASI SAHAM SHARIâAH - Yamoh, Waeabdulrahman (LP2M IAIN Mataram, 2014)
In 2003 Indonesia officially launched Sharia stock exchange. Since then it has been becoming an alternative for Islam people to invest in shares and others product. However, the unclear recognition for Sharia stock exchange in Islam perspective leads to the finite of Islam people in choosing Sharia shares as their investment portfolios. This research applies qualitative method and content analysis to dig out Islam concept upon such value investing. The result of this research depicts that, the choice of investment in stock exchange is a profitable investment instead of another aim to provide businessman to obtain fresh money in developing their company based on profitable sharing principle. Therefore, investment in stock exchange is halal and in line with Islam economy concept. It can be referred to some Islam investment concept such as muda>rabah (participation share), musha>rakah (management share), and mura>bahah (particular kind of share).